1992
DOI: 10.1128/jvi.66.12.7153-7158.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the VP1 coding region of polyomavirus determine differentiating stage specificity

Abstract: Polyomavirus mutants capable of replicating in undifferentiated murine C2 myoblasts were selected and characterized. These mutants grow normally in 3T6 mouse fibroblast cells, and they do not complement the wild-type virus in coinfection experiments of C2 myoblasts. Of 12 isolates, 10 possess duplications of the regulatory region including the enhancer A domain. On the bases of the regulatory region structure and the presence and length of the enhancer duplication, the mutant viruses could be grouped into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Conclusions. These results confirmed our previous report (24) claiming that in vitro host specificity can be determined by both enhancer constitution and VP1 type. We found that the two VP1 mutations selected in undifferentiated myoblast cells also confer to the virus the ability to replicate in undifferentiated embryonal carcinoma F9 cells, strongly indicating that VP1, directly or indirectly, plays a role in viral replication.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Conclusions. These results confirmed our previous report (24) claiming that in vitro host specificity can be determined by both enhancer constitution and VP1 type. We found that the two VP1 mutations selected in undifferentiated myoblast cells also confer to the virus the ability to replicate in undifferentiated embryonal carcinoma F9 cells, strongly indicating that VP1, directly or indirectly, plays a role in viral replication.…”
supporting
confidence: 92%
“…In recent years, several laboratories have investigated the relationship between the genomic variations of mouse polyomavirus (Py) and the tissue specificity of in vitro and in vivo viral replication and oncogenic transformation. In in vitro studies, it was found that host range alteration of replication was due to mutations of the regulatory region (for reviews, see references 2 and 30) except for the two mutants that we isolated in undifferentiated myoblast cells (24). On the other hand, in in vivo studies, both the regulatory region and the major capsid protein VP1 were shown to determine different tissue specificities of replication (1,4,6,9,11,25,31).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Results from our and other laboratories [16–21] had suggested the possibility that VP1, the major capsid protein, could determine alterations in the host specificity of growth and tumorigenicity. In order to determine the possible mechanisms that allow the encapsidated polyomaviruses that reach the cell nucleus to associate with the NM, we investigated the possible role of YY1 in this necessary step of viral function.…”
Section: Introductionmentioning
confidence: 92%